DESIGN WAYPOINT DRONE HEXACOPTER MODEL USING SUGENO FUZZY LOGIC - Akhmad Khoirunnas; Jainur Rahman; Imam Ashar (Merdeka Malang University, 2020)
Fuzzy logic is a scientific branch of Artificial Intelligence that was developed and applied to machines to be able to approach human intelligence. In order this machine or tool to be able to execute commands in a